(NsO^INENIQ(B: [(NdNEWNIKOWYE ZAPISI(B] /s (N~ASTX (B17s - (N~EHOW(B, (NaNTON pAWLOWI^s ((NmOSKWA(B:s (NnAUKA(B,s, 1980)
(Nw (B17 (NTOM SOBRANIQ SO^INENIJ a(B.(Np(B. (N~EHOWA WO[LI DNEWNIKOWYE ZAPISI PISATELQ(B.s
rus
Keywords: (NdNEWNIKIs